Le sens géographique du jardin « individuel » et sa relation au paysage - Cyrille Marlin (Projets de Paysage)
How can the "individual" garden become a part of the objects and tools used by the geographer to apprehend the human environment? How does this question relate to the seemingly wider question of the ways in which the notion of the landscape is used in geography? Singular experiences of gardens observed in Japan, combined with features of Japanese civilisation, are used here to consider the idea of the "individual" garden from a different perspective. More specifically, in reference to its relative absence in the language of geography as opposed to that of the landscape, a historical notion which has accompanied the modern construction of the discipline. The notion of medial interaction is put forward as an essential key to the garden’s conceptual deconstruction and reconstruction in geographical terms. It is the overlapping of the question of the autonomy of individual behaviour in the installation of gardens according to a specific idea of the garden that makes it possible to re-establish a link between the notions of garden and landscape from the geographical perspective of the spatial dimension of the social environment.